DEVELOPMENT OF DEEP LEARNING LEARNING APPROACH IN IMPROVING CRITICAL THINKING SKILLS AND MASTERY OF LANGUAGE CONCEPTS IN GRADE IV STUDENTS OF SDN 16 BANGKALA - Basrawati basra; Munirah; Haslinda (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to develop Indonesian learning tools based on the Deep Learning approach to improve critical thinking skills and mastery of language concepts of elementary school students. The research was carried out at SDN 16 Bangkala, Jeneponto Regency, in the odd semester of the 2025/2026 school year with 25 subjects in grade IV. The development model used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection techniques include observation, interviews, questionnaires, and learning outcome tests. The validation results of three experts showed that the teaching modules developed were classified as very valid with an average feasibility level of 89%. The implementation of learning using Deep Learning syntax (Engage, Explore, Explain, Elaborate, Evaluate) shows an increase in student activity and involvement in the learning process. Based on the results of the data analysis, the average value of critical thinking skills increased from 61.2 to 83.6 with an N-Gain of 0.58 (medium-high category), while the mastery of language concepts increased from 63.4 to 86.8 with an N-Gain of 0.63 (high category). The results of the t-test showed p < 0.05 which means that there was a significant increase after the implementation of Deep Learning-based learning. Thus, it can be concluded that the Indonesian teaching module based on the Deep Learning approach is effective in improving students' critical thinking skills and mastery of language concepts. This approach is able to create learning that is aware, meaningful, and fun, and in line with the principles of the Independent Curriculum which emphasizes differentiated and student-centered learning.